Emotional Awareness: Reflections on the Preoccupation with Emotion Management in Contemporary Scandinavian Societies - Eva Gulløv (Barn)
This article explores the current concern for the mental wellbeing of children and young people. Rather than seeing wellbeing as solely an individual psychological matter, I argue that it should be understood in the light of three pervasive transformations that have altered the social dynamics in Scandinavia over the last 100 years, namely ‘informalisation’, ‘individualisation’ and ‘institutionalisation’. The article shows how these processes have led to a stronger need for individuals to create their own social relationships, but also that confidence in the individual’s ability to do so has gradually decreased. This is evidenced by the large number of professional initiatives and programmes that have been developed in recent years to help children and young people manage their emotions and build relationships in ways that are both true to themselves and considered appropriate by wider society.